THE EFFECT OF LIVE STREAMING AND PRODUCT BUNDLING ON IMPULSE BUYING DECISIONS FOR GLAD2GLOW PRODUCTS ON THE TIKTOK SHOP APPLICATION IN BOGOR REGENCY - Novita Ulan Dari; B.Retno Pratiwi Sakti (STMIK Indonesia Banda Aceh, 2026)
The development of digital technology has changed consumer behavior , especially in online shopping through social media . TikTok Shop utilizes live streaming and product bundling features as marketing strategies to attract consumer interest . Real-time interaction through live streaming and bundling offers are considered capable of encouraging impulsive buying behavior . This study aims to analyze the influence of live streaming and product bundling on impulsive buying decisions for Glad2Glow products on TikTok Shop in the Bogor Regency community . The study used a quantitative approach with a survey method of 100 respondents selected through purposive sampling. Data were collected through questionnaires and analyzed using validity , reliability , hypothesis testing , and linear analysis . The results of the study are expected to contribute to the development of digital marketing science and become a reference for effective marketing strategies for business actors .